Hak Reproduksi Perempuan dalam Islam: Telaah Normatif Dan Dampak Psikologis Pengabaian - Winarni, Winarni; Wardatun, Atun; Purnamasari , Teti Indrawati (Tasyri' : Journal of Islamic Law, 2025)
Women's reproductive rights are an inseparable part of human rights, firmly guaranteed within Islamic teachings. This article aims to examine the normative foundations of women’s reproductive rights in Islam and to analyze the psychological consequences of neglecting these rights within marital life. This study employs a normative and descriptive-qualitative approach based on library research, drawing from classical and contemporary Islamic legal sources as well as relevant psychological literature. The findings show that Islam offers comprehensive protection for women's reproductive roles. Four fundamental rights are emphasized: the right to choose a life partner, the right to enjoy dignified and healthy sexual relations, the right to make conscious and responsible decisions regarding pregnancy, and the right to raise and care for children in a supportive environment. When these rights are denied—either by the spouse or societal structures—women become vulnerable to serious psychological pressures, including chronic stress, depression, loss of self-worth, and in many cases, divorce as a form of resistance against injustice. Promoting awareness and respect for women’s reproductive rights is essential as part of safeguarding the objectives of Islamic law (maqāṣid al-sharī‘ah), especially the protection of life (ḥifẓ al-nafs) and lineage (ḥifẓ al-nasl). This article recommends gender-based education and spiritual approaches to foster mentally healthy, just, and harmonious family life.